Drone thermal imaging and benthic time-series analysis show dynamic spatial and temporal delivery of submarine groundwater discharge on reef ecosystems - Sophia G. Zummo; Lucian Himes; Florybeth F. La Valle (PLoS ONE, 2025)
Submarine groundwater discharge (SGD) introduces nutrient-rich, low-salinity water into coastal ecosystems, significantly altering reef biogeochemistry. At Black Point, Oʻahu, we employed a novel, two-pronged approach that integrates a cost-effective small unmanned aerial system equipped with a thermal infrared (sUAS-TIR) sensor and high-resolution benthic salinity time series to resolve previously unobserved, fine-scale patterns of SGD delivery. sUAS-based sampling overcomes key limitations of prior SGD mapping methods, such as labor-intensive and spatially constrained in situ sampling, by enabling rapid deployment, real-time visualization of mixing dynamics, and high-resolution imagery. Unlike previous studies that relied on customized systems that required independent sensor integration, our methods used a cost-effective, fully integrated sUAS-TIR platform that required no additional modification. Our results show that localized hydrodynamics strongly modulate groundwater delivery, creating spatially heterogeneous patterns of delayed transport, recirculation and retention (i.e., pooling), and offshore dispersal. Thermal imagery revealed persistent surface plumes in regions of reduced circulation, while sequential orthomosaics and benthic salinity time series captured the temporal progression of groundwater movement across the reef. These findings highlight complex SGD delivery patterns that contribute to ecological vulnerability, particularly in areas experiencing prolonged exposure to nutrient-rich, low-salinity waters. Such dynamics underscore the need to consider both spatial and temporal variability when evaluating SGD’s ecological impacts. Our two-pronged approach offers a valuable tool to (1) identify reef zones that may be disproportionately affected by point-sources of land-based pollution, and (2) elucidate the mechanisms driving groundwater transport in coral reef environments. By offering a cost-effective, scalable, and operationally flexible framework, this methodology advances the management of groundwater-impacted ecosystems and enhances our ability to assess the ecological implications of dynamic SGD delivery.